Equality and Freedom in Educational Institutions: An Overview of Religious Tolerance in Indonesia - U. P. Charles Silalahi (Proceeding International Conference on Religion, Science and Education, 2023)
The purpose of this study is to examine religious tolerance in educational institutions from the perspective of John Locke. The main question that guides this research is: how to create religious tolerance in educational institutions in Indonesia? Using an objective historical approach to John Locke's thoughts, the author will review the issue of equality and freedom of religion in Indonesian educational institutions. The main results of this study state that there are still several facts of intolerance in educational institutions in Indonesia. Moreover, political forces deliberately maintain intolerance in educational institutions for the continuity of political power. Politicians exploit social differences as a means of attaining political populism. Thus to avoid intolerance in educational institutions, there must be a strict separation between political power and religion. Religion must be encouraged in the private sphere. Likewise, with religious attributes that should be private, their interests are accommodated in an educational institution within the limits of respecting freedom and equality. Thus, any regional regulations in the form of uniformity according to certain religious symbols must be repositioned because it is not in the spirit of togetherness and diversity.